Two new species of Lathrolestes (Hymenoptera, Ichneumonidae) from Norway, northern Russia and Finland with a key to western Palaearctic species - Reshchikov, Alexey V. (Zootaxa, 2013)
Species of the genus Lathrolestes Förster (Hymenoptera: Ichneumonidae) from western Palaearctic are reviewed. Two new species of Lathrolestes are described, L. nornae sp. n. from Norway and Russia and L. laevipleuris sp. nov. from Finland. An illustrated key to European species is provided. Four additional species are recorded from Norway for the first time.